Political participation of communities in the Legislative General Elections (Pemilu) - Rahmawati Halim; Muhlin Muhlin; Rudi Salam (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The active involvement of the community at all stages of the election is very much needed, because our voice has an important value for the quality of democracy. The purpose of this study was to determine the extent of the political participation of the community in the legislative elections held in the electoral district of Banggai III in Banggai District. This research was conducted in Banggai III election area, which consists of 6 districts; Bualemo, Pagimana, Lobu, Bunta, Nuhon, and Simpang Raya. The study population amounted to 101,296 people. The samples were taken using cluster sampling and random sampling, with a 5% margin of error criteria. The total sample was made up of 236 people. The type of research methodology was a survey. The data was analysed using descriptive and inferential analysis. The methods of data collection were observations, in-depth interviews and questionnaires. The results showed that the political participation of the community involved seven variables: 1) the social and economic status of society, 2) geographic situation; 3) parental affiliation; 4) organisational experience; 5) political knowledge and awareness; 6) trust in the Government and 7) mass media socialisation and informal discussions. The social and economic status variables of the community, the experience of community organising and the trust in the Government should be taken seriously by the Regional Government and the KPU. While the models can provide positive nuances in relation to the political participation of the community such as a model capable of providing nuances such as 1) an improvement in social and economic status, 2) increased access regarding the geographical situation, 3) empowering community groups and affiliated politics, 4) improving the organisational experience of the community, 5) increasing public awareness, 6) increasing public trust to Local Government and DPRD, and 6) empowering mass media and informal discussions